Thorium and Total REE Correlation in Stream Sediment Samples from Lingga Regency - Ronaldo Irzon (EKSPLORIUM, 2018)
Rare Earth Elements (REE) are found in variety of minerals, which are mobilized by weathering from adjacent watersheds into streambeds and affect the chemical content. A study of stream sediments is useful to trace the source of metals, as they are representative of the composition of the drainage basin. This study describes trace and rare earth elements geochemistry composition of selected nine stream sediment samples from two major Islands in Lingga Regency, namely Singkep and Lingga. Moreover, the associations of rare earth elements abundance to other elements in selected samples are used on tracing the most possible mineral as REE source. Nine selected stream sediments were identified megascopically and measured for the trace and rare earth elements composition by inductively coupled plasma – mass spectrometry (ICP-MS). The selected samples from Lingga yielded very strong average Zr, Mn, Ba, and Rb compositions of 246 ppm, 172 ppm, 126 ppm, and 84 ppm, respectively. On the other hand, Zr, Mn, Cr, and Rb are the top four abundant trace elements from Singkep with consecutive median value of 486 ppm, 305 ppm, 145 ppm, and 85 ppm. Feltilizer for agricultural area at Lingga most posibly contain As and Rb upon these elements abundances and association. Tin mine activity was found to influence the streambeds composition with low Rb-Cs composition but high Zr-REE abundance. Very strong Th to ∑REE association suggests that thorium-bearing mineral, especially monazite-La, is the main REE source of the selected samples. All of the studied samples exhibit Eu negative anomaly to imply the absence of either detrital apatite or chemical weathering of apatite. Moreover, REE of Lingga stream sediments is averagely more fractionated than Singkep.  Unsur Tanah Jarang (UTJ) terkandung dalam berbagai jenis mineral yang dapat termobilisasi akibat pelapukan dari daerah aliran sungai terdekat, terendapkan, dan mempengaruhi kandungan kimianya. Studi mengenai sedimen sungai dapat dimanfaatkan untuk menelusuri sumber logam, sebagaimana sedimen tersebut merupakan bahan penyusun dasar sungai. Penelitian ini menerangkan kandungan geokimia unsur jejak dan tanah jarang dari sembilan contoh sedimen sungai terpilih dari dua pulau besar di Kabupaten Lingga, yaitu: Singkep dan Lingga. Selanjutnya, asosiasi kelimpahan unsur tanah jarang terhadap unsur lain dipergunakan untuk menelusuri mineral yang paling mungkin sebagai sumber UTJ. Sembilan contoh sedimen sungai terpilih telah dideskripsi secara megaskopis dan diukur kandungan unsur jejak dan tanah jarangnya menggunakan inductively coupled plasma – mass spectrometry (ICP-MS). Contoh terpilih dari Pulau Lingga tersusun atas sejumlah tinggi Zr, Mn, Ba, dan Rb, yaitu 246 ppm, 172 ppm, 126 ppm, and 84 ppm secara berurutan. Sementara itu, Zr, Mn, Cr, dan Rb merupakan unsur paling melimpah pada contoh dari Pulau Singkep dengan rataan kelimpahan masing-masing 486 ppm, 305 ppm, 145 ppm, and 85 ppm. Pupuk pertanian di Lingga kemungkinan besar mengandung As dan Rbberdasarkan kelimpahan dan asosiasi mineral tersebut. Aktivitas penambangan timah ditengarai mempengaruhi komposisi endapan sungai dengan komposisi Rb-Cs yang rendah tetapi Zr-REE melimpah. Korelasi kuat Th dan ∑UTJ menunjukkan bahwa mineral mengandung thorium, khususnya monasit-La, merupakan sumber utama UTJ pada contoh terpilih. Seluruh contoh menampakkan anomali negatif Eu yang menandakan ketiadaan apatit detrital maupun pelapukan kimia apatit. Lebih jauh, UTJ pada sedimen sungai Lingga secara rata-rata lebih terfraksinasi dari pada Singkep.